ANALISIS KETERSEDIAAN PANGAN KOTA MALANG - Dita Atasa; Tri Wahyu Nugroho (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The research purposes are analyzing food availability, food procurement diversity, and analyzing target formulation, procurement necessity, and food production in Malang in 2016 - 2019. The analysis used is Food Balance Sheet (FBS) and Food Desirable Dietary Pattern (FDDP). The analysis result shows that the food availability in Malang is dominated by plant food source with 81,75 % of percentages. The total of energy availability value is 2.227 kcal/kap/day and protein 63,77 gram/kap/day. The quality of food availability measured with FDDP is 89,33 which shows that food diversity is not maximal yet. Overall, the food availability energy in Malang has not fulfilled Recommended Dietary Energy (RDE) standard and the protein is more than Recommended Dietary Protein (RDP), in which RDE ideal is 2.400 kcal/kap/day and RDP is 63 gram/kap/day. RDE and RDP of ideal food availability can be reached by increasing and decreasing food commodity group gradually from 2016 to 2019. The food commodity groups that need to be increased are such as; cereals, pulse nut and oil seeds, animal food, vegetable, and fruit. While the commodity groups that need to be decreased are such as starchy food, nut, oil and fat, animal food, and sugar.